Union and Firm Preferences for Bargaining Outcomes in the Private Sector - Chaykowski, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
The relative importance that firms and unions place on bargaining issues in the long run is investigated for the Canadian private sector. Survey results suggest that rankings are similarfor some outcomes, but diverge markedly for others. Variations in union rankings are more sensitive to economic conditions than are firm rankings, and union characteristics such as bargaining unit size and percentage of female membership determine union rankings over alternative outcomes, whereas a firm's industrial classification is an important determinant of management priorities.